1989
DOI: 10.1002/lsm.1900090105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CO2 and blood media on laser probe temperature

Abstract: Blood may limit laser ablation of arterial plaque by decreasing thermal energy transfer from metal-capped probes to arterial occlusions. Since a gas is a good insulator of heat, CO2 may be a better medium for laser recanalization. To study this possibility, a metal-capped fiber was positioned in a segment of blood-filled polyethylene tubing and activated with an argon laser. Probe temperatures were measured in blood and as the blood was displaced by flowing CO2 gas. Probe temperatures were higher at all powers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Our previous study also demonstrated that C 0 2 gas perfusion facilitated more effective and safer ablation of human atheromatous plaques than did saline perfusion, even though the latter is usually infused in clinical laser angioplasty when using the sapphire probes (45). The greater laser ablation efficiency was related to 1) better insulation by C 0 2 gas than by saline, resulting in a stronger photothermal effect of laser heat-tissue interaction; 2) more effective removal of blood from the laser irradiation site by C 0 2 gas perfusion; and 3) better penetration of direct laser light through C 0 2 gas than through saline (37,44). Endovascular angioscopy.…”
Section: Application Of C 0 2 Gas In Vascular Interventions and Othermentioning
confidence: 99%
“…Our previous study also demonstrated that C 0 2 gas perfusion facilitated more effective and safer ablation of human atheromatous plaques than did saline perfusion, even though the latter is usually infused in clinical laser angioplasty when using the sapphire probes (45). The greater laser ablation efficiency was related to 1) better insulation by C 0 2 gas than by saline, resulting in a stronger photothermal effect of laser heat-tissue interaction; 2) more effective removal of blood from the laser irradiation site by C 0 2 gas perfusion; and 3) better penetration of direct laser light through C 0 2 gas than through saline (37,44). Endovascular angioscopy.…”
Section: Application Of C 0 2 Gas In Vascular Interventions and Othermentioning
confidence: 99%
“…Our previous study also demonstrated that CO 2 gas perfusion facilitated more effective and safer ablation of human atheromatous plaques than did saline perfusion, even though the latter is usually infused in clinica11aser angioplasty when using the sapphire probes (45). The greater laser ablation efficiency was related to 1) better insulation by CO 2 gas than by saline, resulting in a stronger photothermal effect of laser heat-tissue interaction; 2) more effective removal of blood from the laser irradiation site by CO 2 gas perfusion; and 3) better penetration of direct laser light through CO 2 gas than through saline (37,44). Endovascular angioscopy.…”
Section: Complicationsmentioning
confidence: 99%